DIVING MOTION ESTIMATION OF REMOTELY OPERATED VEHICLE USING ENSEMBLE KALMAN FILTER AND H-INFINITY - Herlambang, Teguh; Suryowinoto, Andy; Adrianto, Dian; Rahmalia, Dinita; Nurhadi, Hendro (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2023)
ROV (Remotely Operated Vehicle) is a product of technological development, functioning to perform tasks in the water. Big tasks such as coral reef exploration, oil refineries, underwater monitoring, and sea accident rescue are carried out by such technology. ROV or unmanned submarines have 6 degrees of freedom, but for diving it requires only 3 movements, that is, surge, heave, and pitch motions. In its operation, the ROV requires a navigation system in the form of estimation of the ROV position under diving conditions. In this study, two methods were used to estimate the ROV position under diving conditions, that is, the H-infinity method and the Ensemble Kalman Filter (EnKF). Both methods proved reliable on other platforms. The simulation results in this study showed that the EnKF method was more accurate than the H-Infinity method. The H-Infinity method had an accuracy of around 87%, while the EnKF method reached an accurate of 99 %.